Keefektifan Modul Elektronik Berbasis Studi Kasus Materi Sistem Ekskresi untuk Melatihkan Keterampilan Hots Peserta Didik - Wulandari, Lisa; Qomariyah, Nur (Universitas Negeri Surabaya, 2025)
Learners in the 21st century are required to master various skills that can be utilized to improve their life skills. Higher Order Thinking Skills (HOTS) is one of the skills that must be mastered by students, but it has not been maximally trained in the learning process. Factors causing the low HOTS skills are the limited number of learning resources and learning resources that have not linked to real events in life so that they have not trained HOTS. Based on this, learning resources that can train HOTS skills are needed. The purpose of this study is to describe the effectiveness of interactive electronic modules based on case studies of excretory system material to train high school students' HOTS skills. This research is a type of development research with the 4D model (define, design, develop, and disseminate). The data collection technique used the test method in the form of pretest and posttest to see the HOTS skills of students in terms of the improvement of HOTS skills and the completeness of HOTS indicators. Students' HOTS skills have increased by referring to the results of the N-Gain calculation which obtained a result of 0.84% in the high category. Indicators of students' HOTS skills experienced completeness by looking at the posttest results where the C4 (analyze) indicator scored 87%, the C5 (evaluate) indicator scored 86%, and the C6 (create) indicator scored 89% with the category achieved by all indicators, namely very complete. Thus, it can be concluded that the case study-based interactive electronic module developed is effective to train the HOTS skills of high school students.